A Qualitative Study Into Mental Health Tutors’ Experiences and Perceptions of Women and Self Harm. - Vincent, Hayley (2009)
The aim of this research study was to explore mental health nursing tutors’ perceptions and experiences of issues surrounding women and self-harm. Between 0.4% and 2% of the population in the UK reports engaging in self-harm and it is thought that 80% of those are female.